FIELD GUIDE TO COMMUNITY LITERACY case studies and tools for praxis. - Henry, Laurie A.; Stahl, Norman A., 1949- ([S.l.] : ROUTLEDGE, 2022)
This practical guidebook presents trends, research-grounded strategies, and field-based solutions to challenges of working in community-based literacy initiatives. A comprehensive guide for practitioners, this book addresses best practices for implementing, maintaining, expanding, and evaluating community-based literacy initiatives. The contributors in this volume help readers shift thinking from merely considering, "How can communities support literacy?" to "How can literacy help us create, support, and strengthen communities?" Organized into four parts - on building community through literacy, program design, case studies from the field, and program evaluation - chapters cover research-based and innovative practices in a diverse range of populations and settings, including family services, adult literacy initiatives, community centers, and tutoring programs. With an abundance of praxis-oriented examples and real-world strategies from top scholars and practitioners, the book serves as a roadmap for essential topics, including funding, writing grant proposals, handling audits, and conducting research within program settings. With templates, models, planning tools, and checklists ready for immediate use, this book is an invaluable field manual for individuals involved in community literacy work, researchers, and students in literacy-oriented courses either at the undergraduate or graduate levels.
Keywords: Literacy programs; LANGUAGE ARTS & DISCIPLINES / Literacy; EDUCATION / Adult & Continuing Education; EDUCATION / Organizations & Institutions